Analysis of the Relationship between Risk Management of Laboratory Test Errors and the Quality of Laboratory Personnel Services at GrandMed Lubuk Pakam Hospital - Selda manullang; Barita Aritonang; Chandra Pranata (JURNAL KESMAS DAN GIZI (JKG), 2026)
Risk management is an essential component of a laboratory quality system to prevent errors in examination results and to improve service quality. This study aimed to analyze the relationship between risk management of laboratory result errors and the service quality of laboratory personnel at GrandMed Hospital Lubuk Pakam. This study employed a quantitative method with a cross-sectional design. A total of 30 respondents were recruited using a total sampling technique. Data were collected using questionnaires and analyzed using the Spearman Rank correlation test. The results show that the type of error is significantly associated with service quality (r = 0.389; p = 0.034), risk identification has a very strong and significant association (r = 0.752; p = 0.000), and risk analysis is significantly associated with service quality (r = 0.382; p = 0.037). However, risk control is not significantly associated (r = 0.156; p = 0.410), and user satisfaction is also not significantly associated (r = 0.052; p = 0.784). Overall, risk management of laboratory errors shows a very strong positive correlation with the service quality of laboratory personnel (r = 0.823; p = 0.000). In conclusion, risk identification and risk analysis are the main factors associated with improving the service quality of laboratory personnel. Therefore, strengthening standard